ISOLATION AND NODULATION TEST OF Rhizobium sp. FROM Pueraria javanica (Benth.) Benth. AND LIABILITY TEST ON THE CARRIER MEDIUM OF PEAT AND COMPOST FROM PALM OIL PALM EMPTY FRUITS - Agnes Siska Situmorang (Lembaga Layanan Pendidikan Tinggi Wilayah I Sumatra Utara (LLDikti I), 2022)
Isolation and Nodulation Rhizobium sp. from Pueraria javanica (Benth.) Benth. and Study of Its Survival on Peat Soil and Compost of Oil Palm Empty Fruit Bunch was done from March to July 2008, in the Laboratory of Plant Biotechnology of Indonesian Oil Palm Research Institute (IOPRI) Marihat Research Station in Pematang Siantar, and Laboratory of Microbiology, Department of Biology, FMIPA USU. The sampel of nodules were taken from the roots of Pueraria javanica growing in the oil palm plantation at Sei Aek Pancur, Marihat, and University of North Sumatera. Ten isolates were isolated from the nodules and all of them could form root nodule after 8 weeks of inoculation in a nodulation trial. Another trial was conducted to study the survival of the Rhizobium in 2 different types of media: peat soil and compost of oil palm empty fruit bunch. It was found that all of the isolates could survive in both media during 4 weeks of observation. Statistically, the Rhizobium had a more stable viability in compost.